Film art an introduction - Bordwell, David; Thompson, Kristin 1950-; Smith, Jeff (Jeffrey Paul) (New York McGraw-Hill Education, 2017)
"Studying the arts isn't only about learning facts and concepts either, although both are important. In addition, studying the arts broadens our tastes. In eleven editions of Film Art, we've made reference to many well-known films but also to many that you've probably never heard of. This is part of our plan. We want to show that the world of cinema teems with a great many unexpected pleasures, and we hope to get you curious"--Provided by publisher.
"Film is an art form with a language and an aesthetic all its own. Since 1979, David Bordwell, Kristin Thompson and now, Co-Author, Jeff Smith's Film Art has been the best-selling and most widely respected introduction to the analysis of cinema. Taking a skills-centered approach supported by examples from many periods and countries, the authors help students develop a core set of analytical skills that will enrich their understanding of any film, in any genre. In-depth examples deepen students' appreciation for how creative choices by filmmakers affect what viewers experience and how they respond. Film Art is generously illustrated with more than 1,000 frame enlargements taken directly from completed films, providing concrete illustrations of key concepts. Along with updated examples and expanded coverage of digital filmmaking, the eleventh edition of Film Art delivers SmartBook, first and only adaptive reading experience currently available, designed to help students stay focused, maximize study time and retain basic concepts." -- Publisher's description.
Film art and filmmaking. Film as art : creativity, technology, and business -- Film form. The significance of film form ; Narrative form -- Film style. The shot: mise-en-scene ; The shot: cinematography ; The relation of shot to shot: editing ; Sound in the cinema ; Summary: style and film form -- Types of films. Film genres ; Documentary, experimental, and animated films -- Critical analysis of films. Film criticism: sample analyses -- Film art and film history. Historical changes in film art: conventions and choices, tradition and trends.
Includes index.
Keywords: Motion pictures -- Aesthetics